PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GOOGLE SITE PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Sironimus, Kristianus Sugianto; Didik Iswahyudi; Yulianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The role of 21st century schools is very important in education, especially in the era of the industrial revolution 4.0 which requires quality improvement through teacher competence and technology integration. However, Pancasila Education learning at SDN Gadang 3 is still conventional, relying on lectures and textbooks, so it is less interesting. Although the facilities are adequate, digital learning media such as Google Sites have not been utilized due to limited teacher capabilities, so that existing facilities are not used optimally. As a result, students feel bored because learning only focuses on sources from textbooks and LKS. This study aims to develop interactive learning media based on Google Sites for Pancasila Education for grade V with a focus on Indonesian cultural diversity. The method used is the Research and Development (R&D) ADDIE model, including analysis, design, development, implementation, and evaluation, involving media, material, language experts, as well as teachers and students for practicality testing. The results of the feasibility test showed that 94.7% of media experts, 87.5% of material experts, and 95% of language experts, indicated "Very Feasible". The practicality test recorded a score of 94.11% from teachers and 88.75% from students, also "Very Practical". The effectiveness test showed a percentage of 59.37% with the category "Effective". In conclusion, Google Sites-based learning media on the Pancasila Education subject, the material on the diversity of Indonesian culture, is very feasible, practical, and effective for use in elementary schools.